Roles of cell division control factor SdiA: recognition of quorum sensing signals and modulation of transcription regulation targets. (19th March 2014) - Shimada, Tomohiro; Shimada, Kaori; Matsui, Makoto; Kitai, Yuichi; Igarashi, Jun; Suga, Hiroaki; Ishihama, Akira
<x xml:space="preserve">Abstract</x> In Gram‐negative bacteria, N‐acylhomoserine lactone (HSL) is used as a signal in cell–cell communication and quorum sensing (QS). The model prokaryote Escherichia coli lacks the system of HSL synthesis, but is capable of monitoring HSL signals in environment. Transcription factor SdiA for cell division control is believed to play a role as a HSL sensor. Using a collection of 477 species of chemically synthesized HSL analogues, we identified three synthetic signal molecules (SSMs) that bind in vitro to purified SdiA. After SELEX‐chip screening of SdiA‐binding DNA sequences, a striking difference was found between these SSMs in the pattern of regulation target genes on the E. coli genome. Based on Northern blot analysis in vivo, a set of target genes were found to be repressed by SdiA in the absence of effectors and derepressed by the addition of SSMs. Another set of genes were, however, expressed in the absence of effector ligands but repressed by the addition of SSMs. Taken together, we propose that the spectrum of taget gene selection by SdiA is modulated in multiple modes depending on the interacting HSL‐like signal molecules.